ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KEBIJAKAN HUTANG - Handayani, Sri Retno; Shaferi, Intan (Faculty of Economics and Business Universitas Jenderal Soedirman, 2013)
One of policies which are related with the continuity of the company’s life is the finance policy. The decision of debt is the finance policy which can be taken because it considers of some influences. This research used return on assets, liquidities, and the measurements of the company as the variables which influenced the policy of debt. The analysis was done to eighteen manufactured companies that were counted in Bursa Efek Jakarta (BEJ) with the research approximate time from 2008-2010. The double linear regression was used in this research with the result that return on assets, liquidities, and the measurements of the company are influential toward debt to equity ratio.